Interplay Polemic between Sindhi Scholars after First World War - Rasool, Ghulam; Kausar Arain, Rehana; Hussain Khatti, Deedar (Al-Amīr Research Journal for Islamic Studies, 2024)
British colonialism in the Indian Subcontinent lasted for two centuries, which empowered the indigenous nations and reformed the education system. Simultaneously, the British influences were top-notch on the Muslim scholars. Besides, modern Indian history is a matter of spacious research investigations with different scholarly studies thickening on diverse aspects of the British colonial Raj, the freedom movements, and the interactive nuisance of the subcontinent politics. Similarly, internal conflicts and dynamics between Muslim scholars/Ulemas in British India, particularly Sindh have mostly been discounted inside the broader historiography. The proposed study focuses on the variance of Muslims that evolved during the colonial period in Sindh. However, the First World War catalyzed a political turning point in oppugning British colonialism and raising anti-colonial movements. During this time, the narrative famously criticized the sun would never set on the British Empire. The spotting embellish how the political contrarieties between two groups of Muslims disagreed during the time. It analyzed examining colonial behavior in order to evolve the altercations and whines in the Muslim community of Sindh. The consequences of this research attempted to understand the research study. This research employed a qualitative mode of inquiry collecting secondary data from published documents, including journals, research papers, books, and reports. It uncovers illustrations where Muslims were found diverged along sectarian and politics through an extensive analysis of historical events and political movements, intricately meshed with the broader framework of British colonialism in India. Keywords: Political Turmoil, Muslim Scholar, Hijrat Movement, Sindh History